Полоса и количество частотных зон селективного преобразования в приемнике мобильного терминала - Ящук, А. С.; Сундучков, К. С.; Волков, С. Э. (Проблеми телекомунікацій, 2012)
Permissible speed of mobile users has increased to 200-300 km/h. Multiservice radio over fiber mm range network allows to provide broadband services (3, 12 Mbts) for a few thousand subscribers moving at high speed (200-300 km/h). Its architecture has specific features, namely facilitation of base station (BS) functions and choosing the optimal topology of communication between the central station and BS-es. These features lead to more complicated mobile terminals (MT) by adding selective allocation of an ordered service from the signal of the whole set of services. Bandwidth of the whole set of services is up to 4 GHz. A method to calculate service allocation parameters in MT capable to work in such network was previously described. However it does not take into account the minimum allowable cell road coverage by BS limitations. The purpose of this paper: to define the parameters of the selective service allocation in MT receiver taking into account a restriction of the minimum allowable cell road coverage served by one BS. The article specifies the mathematical model of a cell coverage calculating taking into account parameters of selective service allocation (zone number and bandwidth). Additional restrictions of selective service allocation parameters in MT were retrieved, namely: bandwidth of the frequency zone cannot be greater than 500 MHz; any BS should have a dual-horn antenna; a modulation QAM-512 for services with speed 12 Mbit/s is unacceptable.
Keywords: радиус соты; селективное преобразование; мобильный терминал